1991
DOI: 10.1128/iai.59.8.2664-2672.1991
|View full text |Cite
|
Sign up to set email alerts
|

Virulence patterns and long-range genetic mapping of extraintestinal Escherichia coli K1, K5, and K100 isolates: use of pulsed-field gel electrophoresis

Abstract: A total of 127 extraintestinal Escherichia coli strains of the capsule serotypes Kl, K5, and K100 from human and animal sources were analyzed for DNA sequences specific for the genes for various adhesins (P fimbriae [pap] and P-related sequences [prs], S fimbriae [sfa]IFIC fimbriae [foc], and type I fimbriae [fim]), aerobactin (aer), and hemolysin (hly). The expression of corresponding virulence factors was also tested. Twenty-four selected strains were analyzed by long-range DNA mapping to evaluate their gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
24
0
3

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 67 publications
6
24
0
3
Order By: Relevance
“…All genera within the family Enterobacteriaceae are capable of producing a layer of strain-specific, surface-associated polysaccharides known as capsule (88). Some forms of capsule have been strongly associated with extraintestinal E. coli infections, including urinary tract infection (45,53,72). The kpsMT genes of CFT073 encode the ATP-binding cassette (ABC) transporter components of the group II capsule gene locus (10), have been associated with virulence in UPEC (29), and were present in a single pyelonephritis strain (CFT204) in the CGH analysis.…”
mentioning
confidence: 99%
“…All genera within the family Enterobacteriaceae are capable of producing a layer of strain-specific, surface-associated polysaccharides known as capsule (88). Some forms of capsule have been strongly associated with extraintestinal E. coli infections, including urinary tract infection (45,53,72). The kpsMT genes of CFT073 encode the ATP-binding cassette (ABC) transporter components of the group II capsule gene locus (10), have been associated with virulence in UPEC (29), and were present in a single pyelonephritis strain (CFT204) in the CGH analysis.…”
mentioning
confidence: 99%
“…Hemagglutination tests and detection of fimbrial adhesins. Hemagglutination in the presence of 1% D-mannose (MRHA) was performed with bacteria grown on CFA agar (12) and with human, bovine, and sheep erythrocytes (12,37). P fimbriae were detected by PF Test (Orion Diagnostika, Espoo, Finland) by agglultnation of a-D-Gal-(1-4)-j3-Galdisaccharide-coated latex particles following the instructions of the supplier.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have shown that only some of the numerous E. coli 0 serogroups are associated with the Kl antigen and that many E. coli Kl strains could be attributed to a small number of clones (2,3). However, E. coli Kl clones were not always uniform in regard to the virulence of strains and geographic differences in clonal predominance and disease were observed (1,3,26,37,51).…”
mentioning
confidence: 99%
“…Plasmid DNA was probed for IS1 sequences and the EcoRI restriction and modi¢cation system (EcoRI R-M). For this purpose the following probes were used: for P ¢mbriae the 4-kb HindIII fragment of plasmid pRHU845 [13]; for S ¢mbriae the 1.8-kb EcoRI/ClaI fragment of plasmid pANN801-13 [13]; for colicin V the 0.4-kb HincII/PvuII fragment of plasmid pHK11 [14]; for the aerobactin uptake system the 2.7-kb SalI/BamHI fragment of plasmid pABN5 [15]; for RepFIB the 1.2-kb PstI fragment of plasmid pULB2404 [16]; for IS1 the 0.25-kb PvuII/BstEII fragment of plasmid pTC72#24 (kindly provided by M. Chandler); for the EcoRI restriction and modi¢cation system the 0.4-kb HindIII/PstI fragment of plasmid pJJC1418 [17].…”
Section: Dna Hybridizationmentioning
confidence: 99%